Blockchain technology for Internet of things: an overview - Cai GUO; Xuran LI; Yanhua CHEN; Hongning DAI (物联网学报)
Internet of things (IoT) is changing the data-driven smart industry due the massive availability of IoT data.Nevertheless, the IoT also poses some challenging issues like decentralization, poor interoperability, privacy and security vulnerabilities.The recent advent of blockchain can potentially tackle the above issues.The marriage of blockchain and IoT was investigated, and named this integration as blockchain of things (BCoT).In particular, the IoT and blockchain technology was introduced firstly.The convergence of blockchain and IoT was introduced, and the proposal of BCoT architecture was presented.The application of the Internet of things in the industry was further discussed.Finally, the open research directions in the field were outlined.